Analysis of distributed interleave‐division‐multiplexing space–frequency codes†. Issue 1 (28th August 2012) - Weitkemper, Petra; Bauch, Gerhard; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT This paper investigates the application of interleave‐division multiplexing (IDM) to a relay network with orthogonal frequency‐division multiplexing (OFDM)‐based radio access. In the proposed scheme, the relay‐specific interleaving is performed on subcarriers in the frequency domain, which is called IDM space–frequency code (IDM‐SFC). It will be shown that IDM‐SFC in combination with OFDM radio access is well suited for distributed deployment of relays, as it is robust to multipath interference and it can achieve full spatial diversity with a constant rate of 1 on the relay–destination hop irrespective of the number of parallel relay nodes. It will be shown that IDM‐SFC outperforms other distributed diversity schemes like OFDM with cyclic delay diversity significantly in various scenarios. In addition to frame error rate analysis, also more theoretical considerations are carried out with the help of extrinsic information transfer charts and signal‐to‐noise power ratio distributions over the subcarrier to provide an insight into the behaviour of the two considered approaches. Copyright © 2012 John Wiley & Sons, Ltd.